Implementasi Kurikulum Berdiferensiasi Ramah Anak (KUBERA) Berbasis Choice Board dalam Menumbuhkan Minat dan Keterlibatan Belajar Siswa Sekolah Dasar - Khairunnisa Erwinsyah, Indri; Sifah Nasution, Syahkira; Nurul Ain, Saskia; Natalia Br Parapat, Trisna; Simanjuntak, Selvi; Istikmalatul Muktamaroh, Asna (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2026)
ABSTRACT This study was motivated by the importance of implementing differentiated learning in the Merdeka Curriculum, which considers elementary school students’ interests, needs, and learning characteristics. Learning activities that tend to be uniform may limit students’ opportunities to choose activities based on their interests. This study aimed to describe the implementation of the Child-Friendly Differentiated Curriculum (KUBERA) based on choice board in fostering elementary school students’ learning interest and engagement. This study used a Research and Development (R&D) method with the 4D development model consisting of define, design, develop, and disseminate stages. The research was conducted in class VA of MIS Al Quba with 20 students as research subjects. Data were collected through observation and documentation. The data were analyzed using descriptive qualitative analysis and simple quantitative analysis through the percentage of students’ activity choices. The results showed that the choice board media provided students with opportunities to choose learning activities based on their interests and learning characteristics. Dancing was chosen by 8 students or 40%, singing by 7 students or 35%, and coloring by 5 students or 25%. These different activity choices indicate the diversity of students’ learning interests. In addition, students’ engagement was shown through their activeness, enthusiasm, self-confidence, and participation during the learning activities. Therefore, choice board media can be used as an alternative child-friendly differentiated learning medium to foster elementary school students’ learning interest and engagement.